2016
DOI: 10.1111/aogs.12898
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injury and incontinence 15–23 years after vaginal delivery

Abstract: OVD was associated with increased risk of OASIS. FD was associated with higher risk of fourth degree perineal tear compared with VD. OASIS was associated with increased risk of anal incontinence and higher CRADI score 15-23 years later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…1 Hence, levator ani muscle injury is related to the appearance of pelvic organ prolapse 1-3 (affecting mainly the anterior and middle compartments 4,5 ) as well as to fecal incontinence during the postpartum period [6][7][8] and in elderly women. 1 Hence, levator ani muscle injury is related to the appearance of pelvic organ prolapse 1-3 (affecting mainly the anterior and middle compartments 4,5 ) as well as to fecal incontinence during the postpartum period [6][7][8] and in elderly women.…”
Section: Introductionmentioning
confidence: 99%
“…1 Hence, levator ani muscle injury is related to the appearance of pelvic organ prolapse 1-3 (affecting mainly the anterior and middle compartments 4,5 ) as well as to fecal incontinence during the postpartum period [6][7][8] and in elderly women. 1 Hence, levator ani muscle injury is related to the appearance of pelvic organ prolapse 1-3 (affecting mainly the anterior and middle compartments 4,5 ) as well as to fecal incontinence during the postpartum period [6][7][8] and in elderly women.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal urgency is defined as having difficulty deferring a sudden or compelling desire to defecate. 5,14,[16][17][18][19][20] The role of planned CS in order to prevent OASIS, AI, and the potential impact of delivery on women's future health remains unclear 1,7,21 A Cochrane Review concluded that planned CS showed no benefit in the prevention of AI in postpartum women. 2,12,13 Furthermore, other studies have shown that AI, in particular, may have a devastating impact on women's social, emotional, and physical activity as well as their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, there has been a significant rise in the incidence of obstetric anal sphincter injury (OASI) over the past two decades. Women with OASI are more likely to be affected by anal incontinence, sexual dysfunction, and impairment of overall quality of life …”
Section: Introductionmentioning
confidence: 99%